South: the endurance expedition - "Shackleton, Ernest" (New York, 2002)
In 1914, as the shadow of war falls across Europe, a party led by veteran explorer Sir Ernest Shackleton sets out to become the first to traverse the Antarctic continent. Their initial optimism is short-lived, however, as the ice field slowly thickens, encasing the ship Endurance in a death-grip, crushing their craft, and marooning 28 men on a polar ice floe. In an epic struggle of man versus the elements, Shackleton leads his team on a harrowing quest for survival over some of the most unforgiving terrain in the world. Icy, tempestuous seas full of gargantuan waves, mountainous glaciers and icebergs, unending brutal cold, and ever-looming starvation are their mortal foes as Shackleton and his men struggle to stay alive. What happened to those brave men forever stands as a testament to their strength of will and the power of human endurance. This is their story, as told by the man who led them.
Keywords: Travel-Antartica